Formulation and antibacterial test traveling paper soap made from virgin coconut oil and durian seeds - Rahmiati; Suciani Zubair; Baiq Yusmi Aolinnir Rahmah; Ika Mustikasari; Annur Afgoni; Erin Ryantin Gunawan (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram, 2022)
Soap as a cleaning product has been the primary needs since the spread of Covid-19. Government regulations require people to wash their hands. Hence the demand for soap production is increasing. This study aimed to obtain a Traveling Paper Soap formulation from VCO and durian seeds for antibacterial activity on the skin. The experimental laboratory method uses quantitative and qualitative descriptive analysis. The treatment in this study was the production of Durian Seed Bioethanol with a bioethanol capacity of 19.95% from the hydrolysis of 486 g of Durian Seed flour. The treatment in this study was the manufacture of durian seed bioethanol with a bioethanol content of 19.95% from the hydrolysis of 486 g of durian seed flour. The parameters of the bioethanol viscosity test were 0.7137 cP, and the bioethanol density was 0.9669 g/mL. Based on our research, the best traveling paper soap results are formulation 2 with a water content of 7%, pH value of 10, free alkali content of 0.21%, and antibacterial activity against Staphylococcus Epidermis of 22.3 mm. According to the Indonesian National Standard Mandatory Solid Soap, SNI 3532:1994, it shows that soap complies with the SNI 3532:1994 standard.